The Women’s Empowerment In Livestock Business Index (WELBI): An Instructional Guide - Omondi, Immaculate A.; Galiè, Alessandra; Teufel, Nils; Kariuki, Eunice (ILRI, 2023)
Developed following the Women Empowerment in livestock Index (WELI) and aligned to the Pro-WEAI for value chains by researchers from the International Livestock Research Institute (ILRI), the WELBI module is a new standardised tool that measures the empowerment of women involved in the livestock-related businesses. This guide offers step-by-step instructions on how to implement the WELBI survey.